2012
DOI: 10.1007/s11434-011-4917-x
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs: Different roles in tumorigenesis

Abstract: A major portion of the mammalian genome is transcribed to produce large numbers of noncoding RNAs (ncRNAs). During the past decade, the discovery of small RNAs, including the microRNAs (miRNA) and small interfering RNAs (siRNA), has led to important advances in biology. The breadth of the ncRNA field of study has substantially expanded and many recent results have revealed a range of functions that can be attributed to the miRNAs and other ncRNAs. For example, H19 RNA, HOTAIR RNA, transcribed ultraconserved re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Thus, the number of primate- or even human-specific miRNAs is large. Due to space limitation, we have not mentioned primate-specific miRNAs that are involved in cancer progression [22] or other cellular functions [57] , [58] .…”
Section: Evolution Of Mirnasmentioning
confidence: 99%
“…Thus, the number of primate- or even human-specific miRNAs is large. Due to space limitation, we have not mentioned primate-specific miRNAs that are involved in cancer progression [22] or other cellular functions [57] , [58] .…”
Section: Evolution Of Mirnasmentioning
confidence: 99%
“…Natural antisense transcripts (NATs), also called antisense RNAs, are RNAs that contain sequences that are complementary to other endogenous transcripts. Antisense RNAs may also encode proteins or may exist only as non-protein-coding transcripts [1] , [2] . In recent years, investigations into NAT functions have indicated that NATs play key roles in carcinogenesis and the development of cancers [3] [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Environmental RNAi has been extensively applied in research with C. elegans, but its application in biotechnology and therapeutics requires further development. Research in environmental RNAi will no doubt be an active branch to continuously bring novel insights in the years to come, as the whole field of noncoding RNA research is moving fast forward [86][87][88][89][90].…”
Section: Resultsmentioning
confidence: 99%